Perform Measuring by Using Image Processing - Sundus Khaleel Ebraheem (Institute of Advanced Engineering and Science, 2016)
The development of ability of the computer leads to improve the abilities of digital image processing, because of the traditional measuring work needs much effort in the site for different fields, and has its difficulties and shortcoming points; therefore this paper introduces improvement for the method to solve the measuring problem, by using digital image processing. This paper improved the system of perform measuring of material for buildings by calculating the volume furthermore the area and dimensions for any position was pointed by the user. The improvement involved in addition to that correction the position of pointed point in case of zooming. The system was designed by using MATLAB R2012b language. The system has implemented on different images and different dimensions as well as on video, it showed accurate results in calculating specific dimensions, areas and volume which defined by the user in the image.